New Approach for Assessing and Improvement of Environmental Management and Strategies in Agri-business (Global Journal of Management and Business Research, 2013)
We suggest a new framework for assessing and improvement of environmental management and strategies in agri-business incorporating interdisciplinary New Institutional Economics. It includes: specification of "managerial needs" and spectrum of governance modes of eco-management at different level of decisionmaking; specification of critical socio-economic, natural, technological, behavioral etc. factors of managerial choice, and feasible spectrum of (private, collective, public, international) managerial strategies; assessment of efficiency of diverse management strategies taking into account the potential to protect eco-rights and investments, assure desirable level of environmental conservation and improvement, minimize overall (implementing, thirdparty, transaction etc.) costs, coordinate and stimulate eco-activities, meet preferences and reconcile conflicts of individuals etc.
Keywords: environmental and natural resources; governance; strategies; institutions; market; private; public modes; agri-business